A BRIEF LITERATURE REVIEW ON THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN CORPORATE REPUTATION - Yadav, Reena; Rana, Taruna; Kaur, Amarjeet; Bhatia, Monika; Singhmar, Arpit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate Social Responsibility has become a strategic tool that businesses are utilizing in order to make their corporate reputation and stakeholder trust environment. This study studies the relationship between CSR and corporate reputation at the sector, country and time levels by examining how the key CSR and corporate reputation relationship. Although a great deal of CSR literature exists regarding the impact of CSR on the corporate reputation, there remains a lot of research gaps. Despite this, most studies have been conducted on particular industries. In addition, there has been geographic concentration of research with scarce focus on emerging economies and developing markets where CSR dynamics may vary based on regulatory, cultural and economic factors. On the methodological side, while previous research relies largely on correlation, regression and Structural Equation Model (SEM), little use of longitudinal studies, experiments and bibliometrics is recommended as another way of methodological advancement. Second, while most investigations show that CSR positively influences corporate reputation, other investigations existing contradictions and argue that there is no correlation or that this correlation is negative under some circumstances.